LaFeO3 perovskite conversion coatings grown on a 13Cr ferritic stainless steel: a corrosion degradation study in simulated solid oxide fuel cell (SOFC) interconnect conditions at 700 °C. Issue 5 (5th December 2016) - Masi, A.; Frangini, S.; Pumiglia, D.; Della Seta, L.; Masci, A.; McPhail, S. J.; Carlini, M.
Abstract : In this work, the corrosion stability of a 13Cr ferritic stainless steel protected by a novel LaFeO3 perovskite conversion coating is studied in demanding solid oxide fuel cell (SOFC) environments. Long‐term degradation behavior of coated 13Cr steel is evaluated and compared with the uncoated steel in air and in dual H2 /air atmospheres at 700 °C. The perovskite coating was found to promote high oxidation resistance during single atmosphere air exposure at 700 °C up to 1800 h, with no signs of coating degradation. Oxidation experiments in dual‐atmosphere environments at 700 °C, carried out with humid hydrogen and air flowing, respectively, on the simulated anode and cathode sides of the sample, led to significant surface iron oxide growth on both coated and uncoated 13Cr steel samples, yet with remarkable difference in corrosion morphology. The coated steel samples suffered from a localized corrosion attack with formation of iron oxide nodules and significant coating detachment, while uniform iron oxide growth was observed on the uncoated steel. The results of this work indicate that the perovskite conversion coating can be a promising approach to protect 13Cr steels in simple oxidizing environments, although further studies and improvements are required for long‐term protection in the more aggressive conditions. Abstract : A novel passivation treatment, carried out at 600 °C in a molten carbonate bath, is exploited to produce a dense La–Fe perovskite conversion coating on a 13Cr ferritic stainless steel. Long‐term tests carried out at 700 °C in air demonstrated high integrity and protective effect of the coating layer. Further improvements in the coating structure are however needed for durable stability and corrosion protection in the much more severe dual atmosphere conditions.